Wheat rhizosphere microbiome: response to application of the Plant Growth Promoting Rhizobacterium Bacillus subtilis T29 and Fusarium pseudograminearum - Korsten, Lise (University of Pretoria, 2022)
Thesis (PhD (Plant Pathology))--University of Pretoria, 2022.